Perioperative nursing care strategies in esophageal cancer surgery: a mini-review - Li, Yu-feng; Tao, Ji-hong; Wang, Chen-chen; Su, De-chun (Frontiers in Oncology, 2025)
This study reviews contemporary clinical trials on perioperative nursing care management (PNCM) in esophageal cancer (EC) surgery. It evaluates four key phases of care: preoperative preparation (patient education and physiological optimization), intraoperative management (physiological monitoring and multidisciplinary team coordination), postoperative care (complication prevention and recovery), and follow-up strategies. Evidence indicates that structured PNCM protocols are associated with improved surgical outcomes. Key interventions include standardized preoperative education programs, intraoperative physiological monitoring protocols, postoperative multimodal analgesia, personalized nutritional supports, and structured rehabilitation pathways. These interventions have demonstrated clinical efficacy, reflected in reduced postoperative complications (especially pulmonary and anastomotic), improved quality-of-life measures, and increased 1-year survival rates. Integration with multidisciplinary surgical teams plays a critical role in optimizing patient outcomes. Future research should prioritize: (1) validating integrated care pathways, (2) personalizing interventions through precise risk stratification, and (3) incorporating technological advances in perioperative care. This review highlights the essential role of specialized perioperative nursing in determining EC surgery outcomes and offers an updated, evidence-based framework to guide both clinical practice and future research.